An Exploratory Study of Health Care Providers’ Acceptance of Opt-Out HIV Testing in Western Australia - Leidel, Stacy Ann (Curtin University, 2017)
In this first study of opt-out HIV testing in Australia, a needs assessment and systematic review of research on opt-out HIV testing indicated a need for a change in testing strategy. Next, a qualitative study of health care providers found dichotomous beliefs about opt-out HIV testing. The final study found that opt-out HIV testing was acceptable, and few patients opted out. Findings from this thesis form an initial evidence base to inform practice, research and policy.